RELATIONSHIP BETWEEN KNOWLEDGE AND ATTITUDE OF POSTPARTUM MOTHERS WITH THE IMPLEMENTATION OF BOUNDING ATTACHMENT IN SIPAHUTAR PUBLIC HEALTH CENTER - Kasmara, Dwi Pratiwi (JURNAL IBU DAN ANAK, 2021)
Bounding attachment is the initial touch or skin contact between mother and baby in the first minutes up to several hours after the baby's birth. This research aims to know the relationship of knowledge and attitude of mother Nifas with the implementation of Bounding attachment in the working area of the community health centers Sipahutar North Tapanuli District year 2020. This research uses crossectional design. The population in the study was all baby mothers in the Sipahutar public healt center for 225 people, and samples of 69 people. Data analysis using Chi Square test. The results showed no knowledge relationship (P = 0,000), attitude (P = 0,003) with the incidence of bounding attachement. To the mother of Nifas be paid to be able to spend time visiting the public healt center to follow the counseling or health promotion about the implementation of Bounding attachment so that pregnant women can have a good knowledge of the benefits of implementing the implementation of Bounding attachment.